Update on the species composition and distribution of sergestid Shrimps (Acetes spp.) in Malaysian waters. - Nurul Amin, Sanker Mohammad; Arshad, Aziz; Siraj, Siti Shapor; Bujang, Japar Sidik (Academic Journals, 2011)
Five species of sergestid shrimps viz., Acetes indicus, Acetes japonicus, Acetes intermedius, Acetes vulgaris and Acetes serrulatus were identified from the different coastal region of Peninsular Malaysia and East Malaysia. Acetes indicus was recorded from the coastal waters of Klebang Besar in the state of Malacca and also in Kuala Gula Perak. The widely distributed shrimp A. japonicus was identified from the coastal waters of Klebang Besar (Malacca), Kuala Gula (Perak), Bagan Ajam (Pulau Pinang), Kuala Sala (Kedah) and Sungai Berembang (Perlis). Acetes intermedius was collected from the coastal waters of Klebang Besar (Malacca), Seberang Takir (Terengganu) and Bintulu (Sarawak). Acetes vulgaris and A. serrulatus were restricted to the coastal waters of Pontian and Kukup in southwestern Johor.